Occult papillary thyroid carcinoma with cystic nodal metastasis mimicking a thyroglossal duct cyst: A case report - Mimery, Alexander (Int J Surg Case Rep, 2019)
INTRODUCTION: The approach to the anterior neck lump involves the consideration of numerous benign and malignant differentials. PRESENTATION OF CASE: We present a rare case of an occult papillary thyroid cancer with cystic nodal metastases presenting as a thyroglossal duct cyst. DISCUSSION: We explore the literature surrounding occult papillary thyroid carcinoma/microcarcinomas and the potential for the disease to present as a cervical lump. There is discussion surrounding the diagnostic and therapeutic difficulties associated with this case, and the importance of lateral thinking and clinical flexibility. CONCLUSION: We recommend that the management approach to any anterior midline neck lump involve a comprehensive work-up including radiological imaging, routine histopathological analysis, and the early involvement of the subspecialty multidisciplinary team.